Radiation and immune checkpoint inhibitors in the treatment of oligometastatic non-small-cell lung cancer: a practical review of rationale, recent data, and research questions - Sondos Zayed; Alexander V. Louie; Daniel A. Breadner; David A. Palma; Rohann J. M. Correa (Therapeutic Advances in Medical Oncology, 2023)
The combined use of stereotactic ablative radiotherapy (SABR) and immune checkpoint inhibitors (ICIs) is an emerging treatment paradigm for oligometastatic non-small-cell lung cancer (NSCLC). Recent phase I and II trial data suggest that SABR to multiple metastases in addition to ICI use is safe and effective with promising progression-free survival and overall survival signals. There is great interest in capitalizing on combined immunomodulation from these two modalities for the treatment of oligometastatic NSCLC. Ongoing trials seek to validate the safety, efficacy, and preferred sequencing of SABR and ICI. This narrative review of the role of SABR when combined with ICI in oligometastatic NSCLC discusses the rationale for this bimodality treatment, summarizes recent clinical trial evidence, and proposes key principles of management based on the available evidence.